“Like a Withered Tree, Stripped of Its Foliage”: What the Roe Court Missed and Why it Matters - Erlich, J. Shoshanna (Columbia Journal of Gender and Law, 2018)
While it would certainly be too much to argue that a fuller exposition of the multi-dimensional origins of the nation’s criminal abortion laws by the Roe Court would have somehow prevented the emergence of the “pro-woman” antiabortion position, I nonetheless contend that if the Roe Court had exposed the gendered origins of our criminal abortion laws, the deep paternalism of the woman-protective approach may well have attracted more critical attention than it did prior to 2007 when the Supreme Court’s embrace of the abortion regret trope served to focus greater public and scholarly attention on this development. In short, this historic knowledge serves to sharpen our understanding of the longstanding link between the regulation of abortion and the effort to control women’s reproductive bodies, thus making it clear that antiabortion activism has never simply been about protecting the fetus. This Article proceeds in three parts. In Part I, we take a close look at the physicians’ mid-nineteenth century campaign to criminalize abortion. Specifically, we will focus on 1) the launch of their campaign; 2) the physicians’ framing of their effort as a “bold and manly” appeal; 3) their focus on preserving and protecting women’s purity and divinely ordained maternal role; 4) their claim that abortion was rife with injurious impacts as embodied in the view that it marked the uterus with a “stamp of derangement”; and 5) the antiabortion physicians’ claim that abortion, as practiced by white, middle-class women, threatened the racial character of the nation. In Part II, we turn to the Court’s landmark decision in Roe v. Wade. Zeroing in on its examination of the historical underpinnings of the nation’s criminal abortion laws, we first take a look at what the Roe Court said about this history, followed by a discussion of what the Court missed—namely, its elision of the gendered and racialized tropes that permeated the physicians’ antiabortion campaign. In Part III, we examine the late twentieth-century emergence of the “pro-woman/pro-life” antiabortion argument. After consideration of the traditional fetal-centric “pro-life” position, we turn to the origins of this new frame. This discussion is followed by a comparison of the core themes of the nineteenth-century physicians’ campaign with the contemporary woman- protective antiabortion position. These themes include: 1) that abortion is incompatible with women’s true nature, 2) that meaningful consent is an impossibility, and 3) that abortion is inherently harmful to women. In conclusion, this Article circles back to the Roe Court’s narrow reading of the physicians’ campaign to argue that if the Roe Court had engaged in a more robust reading of this history, the gendered paternalism of the contemporary “pro-woman/pro-life” position would have been rendered far more visible as a discredited approach to pressing women into motherhood.